Mikkel Faurholdt, Det konservative blodbad, København: Møntergården, 2000, 329 s., kr. 269,00; Niels Krause-Kjær, Kongekabale, København: Gyldendal. 2000, 212 s., kr. 195,00; Ditlev Tamm, Det Høje C, København: Gyldendal^ 1999, 360 s, kr. 400,00. - H. Qvortrup, Mads (Politica, 2000)
-